2014
DOI: 10.1177/0036933014551674
|View full text |Cite
|
Sign up to set email alerts
|

Primary breast osteosarcoma: a case report and review of literature

Abstract: Primary breast osteosarcoma is a rare breast malignancy that affects elderly patients. Diagnosis is often challenging and can be debatable due to its rarity, non-specific radiological findings and the complicated histopathological subtypes. Surgery is the treatment of choice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…As mentioned in the Introduction, primary breast osteosarcoma is a rare malignancy, with approximately 100 cases described in the existing literature through isolated case reports and small case series [3] , [4] , [5] , [6] . Many of the published case reports have shown large calcified masses that presented as palpable abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned in the Introduction, primary breast osteosarcoma is a rare malignancy, with approximately 100 cases described in the existing literature through isolated case reports and small case series [3] , [4] , [5] , [6] . Many of the published case reports have shown large calcified masses that presented as palpable abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemistry indicated the presence of vimentin without epithelial markers [23] . The diagnostic criteria for osteosarcoma is the absence of epithelial component in the tissue with neoplastic osteoid element [20,24–28] .…”
Section: Primary Osteosarcoma Of the Breastmentioning
confidence: 99%
“…Over a period of 18 years, Jernstorm et al (4) observed only one case of osteosarcoma in 3,319 cases of mammary carcinoma. Treatment for localized disease includes complete surgical removal of the tumor with an adequate margin, whereas chemotherapy is the main treatment for metastatic osteosarcoma (5). To the best of our knowledge, there is no standard adjuvant treatment for breast osteosarcoma at present.…”
Section: Introductionmentioning
confidence: 99%